Pengaruh Citra Merek dan Harga terhadap Loyalitas Konsumen pada Mixue di Daerah Istimewa Yogyakarta - Yasinta Defriani Astin; Nanda Novita Sari; Kristiana Sri Utami (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aimed to analyze the influence of price and brand image on Mixue consumer loyalty in Yogyakarta. Employing a quantitative approach with 50 respondents, data were collected through questionnaires and analyzed using multiple linear regression. Validity and reliability tests demonstrated a robust research instrument. Classical assumptions were met. The F-test indicated a significant simultaneous effect of price and brand image on consumer loyalty (p < 0.05). However, the t-test showed that only brand image had a significant partial effect (p < 0.05), while the effect of price was insignificant (p > 0.05). This finding has implications for Mixue's marketing strategy in Yogyakarta, emphasizing the importance of a strong brand image.